Suspension of the Implementation of International Treaties during Armed Conflict - Al Naqbi, Sheikha; Al Jahani, Abdul Nasser (Journal of Legal Sciences, 2026)
This research focuses on the suspension of the implementation of an international treaty as a result of the outbreak of an armed conflict between its parties, or between one of the parties to the conflict and a third party. The suspension of the implementation of international treaties during armed conflict is a complex issue that addresses the balance between states’ legal obligations and security necessities during times of crisis. International treaties, such as human rights treaties and humanitarian law treaties, are often affected during armed conflicts. The International Law Commission adopted the Draft Articles on the Effects of Armed Conflicts on Treaties, which include several situations that may be relied upon to suspend the implementation of an international treaty during armed conflict. This research highlights the cases of suspension of treaty implementation during armed conflict in accordance with the Draft Articles of the International Law Commission on the Effects of Armed Conflicts on Treaties, as well as the relevant provisions of the Vienna Convention on the Law of Treaties. The research concludes that there are cases stipulated in the Draft Articles of the International Law Commission on the Effects of Armed Conflicts on Treaties that may contribute to the suspension of treaty implementation during armed conflict. However, there are shortcomings in the provisions governing these cases, which may be addressed through recourse to the relevant general provisions contained in the Vienna Convention on the Law of Treaties.